Formation of Eco-friendly Silver Nanoparticle Microalgae using Chlorella vulgaris - Hermin Pancasakti Kusumaningrum; Muhammad Zainuri; Widianingsih Widianingsih; Wahyu Dewi Utari Haryanti; Indras Marhaendrajaya; Robertus Triaji Mahendrajaya (Marine Science Department Diponegoro University, 2019)
Biosynthesized silver nanoparticles (AgNPs) using organism have spurred great interest as a antimicrobial and biomedical agents. Green microalgae have advantages as they are easily available, grow rapidly and producing varieties metabolites. Synthesized of AgNPs from microalgae C. vulgaris offer environmentally antimicrobial agent. The objectives of the study is producing AgNPs microalgae using C. vulgaris as eco-friendly antimicrobial agent. The research methods was conducted by synthesizing silver nanoparticle microalgae using C. vulgaris following by characterization under UV–visible spectroscopy, transmission electron microscopy (TEM), and scanning electron microscope (SEM) and Energy-dispersive X-ray spectroscopy (EDX). The research result showed AgNPs C. vulgaris microalgae were produced with and without agitation treatment under different condition. The synthesized AgNPs C. vulgaris exhibited a maximum absorption at 312 nm and 398 nm, and EDX analysis had determined that abundance chemical elements presented in a sample were carbon and silver. The TEM analysis revealed that they are spherical form. The spot of EDX analysis showed the presence of silver atoms. The SEM analysis shows the spherical shaped with some silver particle inside of the cell. These resut indicated that formation of silver nanoparticle microalgae using C. vulgaris has been succesfully obtained under the treatment.